(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The origin and evolution of the family Pseudostaffellidae is discussed, based on the study of foraminifers from the stratotype and reference sections of the Bashkirian stage of the Southern Urals. Primitive Plectostaffella gave rise to two lineages: one lineage produced Semistaffella-Pseudostaffella, whereas the other lineage produced more advanced Plectostaffella-Varistaffella gen. n. The species from the Southern Urals assigned to Varistaffella are described.